Allium nerimaniae (Amaryllidaceae), a new species of A. sect. Codonoprasum from Turkey - Koçyi̇ği̇t Mine; Kaya, Erdal (Phytotaxa, 2020)
Allium nerimaniae from Van (East Anatolia) is described and illustrated. It is compared with the related Allium hirtovaginum according to distinct morphological characteristics. The seed morphology and leaf anatomy of A. nerimaniae and A. hirtovaginum are also presented and discussed. A key for identification of the hairy taxa of sect. Codonoprasum is presented.